Integrative Model of Digital Marketing Elements on Purchase Intention: The Mediating Role of Electronic Word-Of-Mouth - Ekasari, Silvia; Surip, Ngadino; Muharam, Hari (Yayasan Riset dan Pengembangan Intelektual, 2024)
The beauty industry in Indonesia is experiencing rapid growth, driven by increasing self-care awareness, social media influence, and product innovation. Facial serums are among the most popular products, with sales growth of 36.4% in August-September 2023. Skintific, a local brand offering facial serums, faces stiff competition from Wardah, which continues to lead the market as of June 2023. Additionally, consumer interest in synthetic products has declined, influenced by factors such as price perception, brand image, celebrity endorsers, and online promotions. In the digital era, electronic word of mouth (e-WOM) has become critical in shaping purchasing interest, as online product reviews, testimonials, and discussions significantly impact consumer perceptions. This study examines the role of e-WOM as a mediator in the relationship between digital marketing elements and consumer buying interest. A quantitative approach with descriptive verification was employed, using primary data collected from 397 female students at Depok Higher Education through a convenience sampling technique. Data analysis was conducted using the Structural Equation Model (SEM) with Lisrel software. The findings show that price perception, brand image, celebrity endorsers, and online promotions directly and positively influence both e-WOM and buying interest. Moreover, e-WOM significantly mediates the effect of these marketing factors on purchasing interest. The research introduces an integrative model for enhancing consumer buying interest in Skintific products, with a strong influence level of 90%.